Perancangan dan Pengembangan Vıdeo Company Profıle Vıhara Dharma Mulıa Batam - Tony Wibowo; Jeremy Riantono (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
In this article, we will discuss the design and manufacture of video company profile in the city of Batam called Vihara Dhrama Mulia Batam. The purpose of this society service is to promote the environment and activities of Vihara Dharma Mulia Batam through a platform called Youtube, because there is no promotion of Vihara Dharma Mulia Batam in the form of a company profile video, so it is still not very well known among the wider community. Therefore, the author decided to make video company profile using the Multimedia Development Life Cycle (MDLC) method. Vihara Dharma Mulia Batam company profile video design using Adobe Premiere Pro 2020 and Adobe After Effects software, with a duration of four minutes and forty-two seconds, 1920x1080 resolution using a laptop with Intel® Core™ i7-7700HQ, GTX 950M, and 16GB RAM specifications The result of this scientific project is an increase in popularity and the introduction of Vihara Dharma Mulia Batam